Effects of elastic foundation on the large-amplitude vibration analysis of functionally graded GPL-RC annular sector plates - Ashraf, Muhammad Ageel (Springer, 2022)
The main purpose of this research is to investigate the impacts of the two-parameter elastic medium on the geometrically nonlinear free vibration of nanocomposite annular sector plates reinforced with graphene platelets. The modified Halpin-Tsai micromechanical model is implemented to determine the overall mechanical properties. With the aid of Hamilton's principle and in according the first-order shear deformation plate theory in conjunction with geometric nonlinearity effects, the nonlinear sets of motion equations are derived for functionally graded nanocomposite annular sector plates. The 2D generalized differential quadrature GDQ method, the harmonic balance method and Newton-Raphson iteration technique are utilized to numerically solve the problem and obtain the nonlinear vibration response. Multiple comparative investigations are provided to express the efficiency of the model. The impacts of involved geometrical and material factors are also examined on the nonlinear vibration behavior of functionally graded nanocomposite annular sector plates.